Uniformity of rotavirus strain nomenclature proposed by the Rotavirus Classification Working Group (RCWG) - Matthijnssens, Jelle; Ciarlet, Max; McDonald, Sarah M.; Attoui, Houssam; Bányai, Krisztián; Brister, J. Rodney; Buesa, Javier; Esona, Mathew D.; Estes, Mary K.; Gentsch, Jon R.; Iturriza-Gómara, Miren; Johne, Reimar; et al. (Archives of virology, 2011)
In April 2008, a nucleotide-sequence-based, complete genome classification system was developed for group A rotaviruses (RVs). This system assigns a specific genotype to each of the 11 genome segments of a particular RV strain according to established nucleotide percent cutoff values. Using this approach, the genome of individual RV strains are given the complete descriptor of Gx-P[x]-Ix-Rx-Cx-Mx-Ax-Nx-Tx-Ex-Hx. The Rotavirus Classification Working Group (RCWG) was formed by scientists in the field to maintain, evaluate and develop the RV genotype classification system, in particular to aid in the designation of new genotypes. Since its conception, the group has ratified 51 new genotypes: as of April 2011, new genotypes for VP7 (G20-G27), VP4 (P[28]-P[35]), VP6 (I12-I16), VP1 (R5-R9), VP2 (C6-C9), VP3 (M7-M8), NSP1 (A15-A16), NSP2 (N6-N9), NSP3 (T8-T12), NSP4 (E12-E14) and NSP5/6 (H7-H11) have been defined for RV strains recovered from humans, cows, pigs, horses, mice, South American camelids (guanaco), chickens, turkeys, pheasants, bats and a sugar glider. With increasing numbers of complete RV genome sequences becoming available, a standardized RV strain nomenclature system is needed, and the RCWG proposes that individual RV strains are named as follows: RV group/species of origin/country of identification/common name/year of identification/G- and P-type. In collaboration with the National Center for Biotechnology Information (NCBI), the RCWG is also working on developing a RV-specific resource for the deposition of nucleotide sequences. This resource will provide useful information regarding RV strains, including, but not limited to, the individual gene genotypes and epidemiological and clinical information. Together, the proposed nomenclature system and the NCBI RV resource will offer highly useful tools for investigators to search for, retrieve, and analyze the ever-growing volume of RV genomic data.